Combination of Six Individual Derivatives of the Pom-1 Antibiofilm Peptide Doubles Their Efficacy against Invasive and Multi-Resistant Clinical Isolates of the Pathogenic Yeast Candida albicans - Michelle Häring; Valerie Amann; Ann-Kathrin Kissmann; Tilmann Herberger; Christopher Synatschke; Nicole Kirsch-Pietz; Julio A. Perez-Erviti; Anselmo J. Otero-Gonzalez; Fidel Morales-Vicente; Jakob Andersson; Tanja Weil; Steffen Stenger; et al. (MDPI AG, 2022)
In previous studies, derivatives of the peptide Pom-1, which was originally extracted from the freshwater mollusk Pomacea poeyana, showed an exceptional ability to specifically inhibit biofilm formation of the laboratory strain ATCC 90028 as a model strain of the pathogenic yeast Candida albicans. In follow-up, here, we demonstrate that the derivatives Pom-1A to Pom-1F are also active against biofilms of invasive clinical C. albicans isolates, including strains resistant against fluconazole and/or amphotericin B. However, efficacy varied strongly between the isolates, as indicated by large deviations in the experiments. This lack of robustness could be efficiently bypassed by using mixtures of all peptides. These mixed peptide preparations were active against biofilm formation of all the isolates with uniform efficacies, and the total peptide concentration could be halved compared to the original MIC of the individual peptides (2.5 µg/mL). Moreover, mixing the individual peptides restored the antifungal effect of fluconazole against fluconazole-resistant isolates even at 50% of the standard therapeutic concentration. Without having elucidated the reason for these synergistic effects of the peptides yet, both the gain of efficacy and the considerable increase in efficiency by combining the peptides indicate that Pom-1 and its derivatives in suitable formulations may play an important role as new antibiofilm antimycotics in the fight against invasive clinical infections with (multi-) resistant C. albicans.